Deconcentration of the central state and configuration of power in the territories: institutional change in Ecuador, 2007-2017 - Madrid Tamayo, Andrea (2023)
This article analyzes the impulse given to deconcentration during the Government of the Citizen Revolution in Ecuador (2007-2017) and within the framework of the institutional change that was one of the main elements of the State reform. This government developed a strategy of public administration deconcentration that projected the possibility of bringing the Executive Branch closer to the territories in terms of services, public resources, planning and decision-making. This research contains a qualitative approach based on interviews with former authorities and former officials of the National Secretariat of Planning and Development (SENPLADES), the national entity responsible for implementing State reforms and institutional changes. The study also used SENPLADES’ technical tools and documents to collect information. Despite the efforts, the applied public policies failed to deconcentrate decision making processes.